A VISÃO DOS FORMADORES SOBRE A FORMAÇÃO DO PEDAGOGO NUMA PERSPECTIVA CRÍTICA NO CONTEXTO DAS REFORMULAÇÕES CURRICULARES - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
This study talks about the critic formation of the educator in the context of national curricular reformulations, having as aims: analyze the critical formation of the educator in the context of teaching subjects reformulations; analyze the National Curricular Directives for Elementary Education, the National Curricular Directives for Pedagogy Course and the Pedagogic Project of a course, which expresses the critic formation in the teaching graduation; know the process of elaboration of the Pedagogical Project of the course and the main changes carried out as well as investigate the comprehension of teachers and coordinators about the critic formation of the educator. This research is part of a wider study project sponsored by CNPq entitled “Learning of the Teaching Competence in Licentiates in the context of changes in the Teaching Courses”, which is done by the program of Post-Graduation in Education – Mastership, from the State University of Ponta Grossa. The methodological approach of the research is qualitative, whose procedures of information collection are based on the documental researches and on semi-structured interviews with the ones responsible for the formation of the chosen course. The collected data was taken to analysis and confronted with the theorical referentials of the Critic Pedagogy, from the contributions of Giroux, Contreras and Freire. We obtained nine analysis units: the relation theory and practice; the research as essential element in the teachers´ graduation; the speeding of PPC elaboration; the discontinuity of participation of the professors; the non-definition of the course identity and the curricular structure; the absence of schools in the PPC elaboration; the critic formation and its different conceptions; a more articulated course; the institutional conditions. Summing up the analyzed information, we confirmed the necessity of thinking about the critic formation of the educator being desired by the collective educators and based on emancipator perspectives, which enable reading of the world and some reading of the school to the educator.
Keywords: formação do pedagogo; Diretrizes Curriculares Nacionais, letramento docente; Pedagogia; formation of the educator; National Curricular Directives; teaching literacy; Pedagogy; CNPQ::CIENCIAS HUMANAS::EDUCACAO